AGRICULTURAL AND RURAL DEVELOPMENT GOVERNANCE AND COORDINATION IN BOSNIA AND HERZEGOVINA - Berjan, Siniša; El Bilali, Hamid; Janković, Snežana; Radosavac, Adriana (Economics of Agriculture, 2015)
Rural economy in Bosnia and Herzegovina (BiH) is increasingly diversifed but agriculture is still important. Governance influences agricultural and rural development (ARD) policy impacts. The paper aims at analysing ARD governance and coordination in BiH. The paper is based on primary information collected by questionnaires and semi-structured interviews performed in 2011 with representatives of 120 institutions as well as a secondary data review. Vertical coordination between State level institutions with entities, cantons, regions, municipalities and non-state actors, especially civil society ones, is still particularly challenging. Coordination between the State Ministry of Foreign Trade and External Relations; Ministries of Agriculture of the Republika Srpska (RS) and Federation of BiH (FBiH) and the Department for Agriculture of Brčko district is crucial. Participation of civil society organizations in ARD policies design and evaluation should be encouraged. Effectiveness of vertical coordination also depends on quality of horizontal coordination at RS and FBiH levels.